2021
DOI: 10.21203/rs.3.rs-964107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking emotional valence and anxiety in a mouse insula-amygdala circuit

Abstract: The response of the insular cortex (IC) and amygdala to stimuli of positive and negative valence were found to be altered in patients with anxiety disorders. However, the coding properties of neurons controlling anxiety and valence remain unknown. Combining photometry recordings and chemogenetics in mice, we uncover the anxiogenic control of projection neurons in the anterior IC (aIC), independently of their projection target. Using viral tracing and ex vivo electrophysiology, we characterize the monosynaptic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 29 publications
3
26
1
Order By: Relevance
“…The BLA is one of the main targets of IC projection neurons [13, 30, 31], although their role in the control of water intake remains unclear. As we found that pIC excitatory neurons are active during water licking, that CB 1 receptors in pIC cells regulate drinking behavior and that CB 1 mRNA is expressed in pIC-BLA projection neurons, we hypothesized that pIC-BLA projection neurons selectively respond to water consumption and control water intake.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The BLA is one of the main targets of IC projection neurons [13, 30, 31], although their role in the control of water intake remains unclear. As we found that pIC excitatory neurons are active during water licking, that CB 1 receptors in pIC cells regulate drinking behavior and that CB 1 mRNA is expressed in pIC-BLA projection neurons, we hypothesized that pIC-BLA projection neurons selectively respond to water consumption and control water intake.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that these two neuronal populations oppositely code drinking behavior. A recent study reported that aIC-BLA projection neurons decrease activity when mice lick sucrose, whereas aversive stimuli including mild foot shock and tail suspension produce an increase in activity of these neurons [30]. This suggests that aIC-BLA projection neurons code for negative valence, which in the context of water intake could be associated with thirst.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations